The effect of globalization and the impact of hegemony in "The White Tiger" and "Americanah" novels - Al-Tameemi, Tahseen Ali Ahmed (2023)
This study was conducted to examine the critical attitudes of Aravind Adiga and Chimamanda Ngozi Adichie as authors of the selected literary novels "The White Tiger" (2008) and "Americanah" (2013). The two novels harshly criticized the unstable, inequitable, and miserable social and economic circumstances of third-world individuals in the twenty-first century. The study explored the opinions of the authors, in which Adiga, in "The White Tiger," adopted the critical approach mode to show the negative effects of globalization on Indian society, while in "Americanah," Adichie depicted the resistance to various hegemonies in Nigeria, America, and England. Adiga and Adichie saw globalization and hegemony as exploitative and oppressive social systems towards third-world people. The study relied on post-colonial and Marxist theories based on Gayatri Spivak, Gauri Viswanathan, and Antonio Gramsci’s views on criticism of the two theories (Globalization and Hegemony). This study emphasized the effects of global culture and global identity and the impact of class struggle and poverty on Third World societies. This study employed a qualitative method for data collection. The thematic analysis was conducted to analyze the two novels. In addition, "Excel" file charts were prepared for each novel for sorting and counting the findings. The analysis focused on the critical tone, subject matter and widespread popularity, which were essential aspects of the study. The study found the power of criticism as a subversive weapon against global culture and global identity in the context of globalization and class struggle and poverty in the context of hegemony. The study concluded that Adiga and Adichie were just voices against the socioeconomic injustice, exploitation, oppression, and discrimination of the poor, resulting in servitude. The study contributed by providing a new framework for combining the two theories of globalization and hegemony to clearly map the social and economic changes in the world to encounter class struggle, poverty, and servitude